A Bifunctional Bulky Thienothiophene Derivative; Synthesis, Electronic‐Optical Properties and OLED Applications. Issue 42 (16th November 2020) - Isci, Recep; Tekin, Emine; Mucur, Selin P.; Ozturk, Turan
Abstract: Applying thienothiophenes (TT) as a linker, a bulky bifunctional thienothiophene, TT‐TPA‐TPE3, possessing triphenylamine (TPA) and tetraphenylethylene (TPE) units, was designed, synthesized, and fully characterized. Its optical and electronic properties were explained by UV‐Vis spectroscopy, cyclic voltammetry (CV) and Aggregation‐Induced Emission (AIE) study. TT‐TPA‐TPE3 exhibited positive solvatochromism in the range of solvent polarities from DMF to toluene, displaying emissions from yellowish to bluish between 480–525 nm. Utilizing TT‐TPA‐TPE3 as a hole‐transporting layer, its organic light emitting devices (OLEDs) were fabricated and their performances were investigated. The synthesized emitter exhibited green and blue emissions in device applications. A mega Stoke's shift of 114 nm in THF and a large Stoke's shift of 78 nm on ITO were observed. A maximum luminance of 580 cd m −2 and a turn‐on voltage of 7.01 V were obtained, indicating that TT‐TPA‐TPE3 has a good hole‐transporting ability. Abstract : A bifunctional thienothiophene derivative possessing TPA and TPE units was successfully synthesized, properties of which were investigated through UV, fluorescence, Solvatochromism, and CV studies; its OLED and HTM devices were fabricated.